Strategi Dividen yang Efektif: Memahami Keseimbangan antara Kondisi Keuangan dan Peluang Investasi untuk Pertumbuhan Laba Perusahaan - Rahmadania, Fina (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
In complex business dynamics, dividend policy strategy is a key element that influences company growth and competitiveness. An effective balance between financial conditions and investment opportunities is the main focus to achieve sustainable profit growth. This research aims to understand effective dividend strategies by exploring the optimal balance between a company's financial condition and investment opportunities as a critical step towards sustainable profit growth. The type of research used is associative quantitative. The data used is secondary data obtained from the Indonesian Stock Exchange for the research period. Sample selection was carried out based on the purposive sampling method. This research reveals that an effective dividend strategy requires a deep understanding of the balance between finance and investment. A dividend policy that is appropriate to financial conditions and supports investment opportunities can make a positive contribution to company profit growth.